2017
DOI: 10.1038/s41559-017-0417-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the Tasmanian tiger provides insights into the evolution and demography of an extinct marsupial carnivore

Abstract: The Tasmanian tiger or thylacine (Thylacinus cynocephalus) was the largest carnivorous Australian marsupial to survive into the modern era. Despite last sharing a common ancestor with the eutherian canids ~160 million years ago, their phenotypic resemblance is considered the most striking example of convergent evolution in mammals. The last known thylacine died in captivity in 1936 and many aspects of the evolutionary history of this unique marsupial apex predator remain unknown. Here we have sequenced the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
121
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 109 publications
2
121
2
Order By: Relevance
“…Their skulls in particular were nearly identical in shape (Fig. 1C,D), and this similarity is strongly associated with their carnivorous feeding ecologies (Wroe and Milne 2007;Feigin et al 2018). The thylacine occupied a similar niche in Australia to that filled by canids elsewhere in the world, that of an apex predator specialized in killing vertebrate prey (Jones and Stoddart 1998).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Their skulls in particular were nearly identical in shape (Fig. 1C,D), and this similarity is strongly associated with their carnivorous feeding ecologies (Wroe and Milne 2007;Feigin et al 2018). The thylacine occupied a similar niche in Australia to that filled by canids elsewhere in the world, that of an apex predator specialized in killing vertebrate prey (Jones and Stoddart 1998).…”
mentioning
confidence: 85%
“…Indeed, direct competition with dingoes may have contributed to their extinction on the mainland (Letnic et al 2012). Previous morphometric analyses showed that much of the cranial morphospace between the thylacine and wolf was closed by convergent evolution (Feigin et al 2018). However, the genomic changes underlying this convergence are still unclear.…”
mentioning
confidence: 99%
“…Many cancer centres in the United States therefore offer complementary therapies for pain relief. Almost 90% of US National Cancer Institute-designated cancer centres suggest that patients try acupuncture, and just over 70% offer it as a treatment for side effects 1 . That horrifies sceptics such as Steven Novella, a neurologist at Yale University School of Medicine.…”
Section: By J O M a R C H A N Tmentioning
confidence: 99%
“…By using the sequentially Markovian approximation, and derived methods implicitly assume that genomic information is contiguous. While initially applied to human datasets, which have very high contiguity, and ′ have since been applied to many non-model organisms where the contiguity of genomic sequences may be poor (Zhao et al , 2013; Dobrynin et al , 2015; Mays et al , 2018; Kozma et al , 2016; Feigin et al , 2018). In particular, demographic history is regularly inferred from a de novo assembly as part of genome sequencing projects.…”
Section: Introductionmentioning
confidence: 99%